List of Vespidae, Scoliidae and Tiphiidae (Hymenoptera) of Gölcük Natural Park in Isparta Province, Turkey - George Japoshvili; İsmail Karaca (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2010)
Vespidae, Scoliidae and Tiphidae were collected during 2008-2009 in Gölcük Natural Park, which belongs to Isparta Province. The material was collected by pitfall, yellow pan and malaise trapping methods. Additionally we include data from material collected previously and housed in the entomological museum of the agriculture Faculty of Süleyman Demirel University (EMIT). 26 species from 16 genera were recorded during this survey (19 species from 12 genera of Vespidae, 5 species from 3 genera of Scoliidae and 2 species from 1 genus of Tiphiidae). 16 species were recorded for the first time from Isparta Province.